2014
DOI: 10.1177/1073191114524016
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an Online, Multicomponent Working Memory Battery

Abstract: Research has demonstrated strong connections among working memory (WM), higher-level cognition, and academic achievement. Despite the importance of WM, currently available WM tests have practical limitations and lack comprehensive coverage of multiple WM components. The Working Memory Battery (WOMBAT) includes nine subtests measuring multiple content domains and processing demands, in accordance with contemporary WM theoretical frameworks. The current study evaluated the WOMBAT factor structure and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…On a separate occasion they were administered the WOMBAT (Working Memory Battery; Englund, Decker, Woodlief, & DiStefano, 2014). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On a separate occasion they were administered the WOMBAT (Working Memory Battery; Englund, Decker, Woodlief, & DiStefano, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Participants completed four memory tasks, which are components of a larger Working Memory Battery that includes nine subtests (WOMBAT; Englund et al, 2014). The WOMBAT is a multicomponent test battery that measures separate Verbal, Static Visual-Spatial, and Dynamic Visual-Spatial domains across three levels of processing demands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive tests were administered using a laptop because previous studies confirmed the use of a computer and specific software as a valid and reliable method to assess different cognitive outcomes (Budde et al, 2008;Conners et al, 2008;Englund, Decker, Woodlief, & DiStefano, 2014;Gualtieri & Johnson, 2006;Hanania & Smith, 2010;Ma et al, 2015;Richardson, 2007 …”
Section: P L Invernizzi Et Almentioning
confidence: 99%
“…However, because of the limited capacity of WM, the amount of information and the longevity of its existence depends upon WM span [4]. Historically, it was believed that WM is a heritable construct and is resistant to change, but recent research has affirmed that WM is malleable [5]. It has been suggested that WMC can be expanded by different cognitive, interactive, and computerized tasks, such as repetition, memorization with consciousness, chunking, and the use of multimedia [6].…”
Section: Introductionmentioning
confidence: 99%